Moving Analysis with Indonesian Language Book Class V Elementary School Based on BSNP and EYD Edition V - mahardika, almaida clarissa; Naila Patiha Sari; Muhamad Najmi Mafachir; Pradita Rindayani; Panca Dewi Purwati (Program Studi Tadris Bahasa Indonesia Institut Agama Islam Negeri Lhokseumawe, 2025)
This study aims to analyze the suitability and linguistic quality of the Indonesian Language book Bergerak Bersama for fifth grade elementary school students based on content suitability standards according to the National Education Standards Agency (BSNP) and the rules of Indonesian Spelling (EYD) Edition V. This study uses a qualitative descriptive analysis method with an evaluative approach. The analysis focused on four main aspects, namely content, language, presentation, and graphics, as well as linguistic studies at the syntactic, semantic, morphological, discourse, and phonological levels. The results of the study show that in terms of content, this book is in accordance with the learning elements and learning outcomes (CP), and contains themes that are relevant to the context of students' lives, such as empathy, anti-bullying, and language skills. In terms of language, the majority of the spelling, sentence structure, and punctuation are in accordance with EYD Edition V, although some minor errors were found, such as the use of punctuation and sentence structure that are not effective. Linguistically, this book is consistent in its use of sentence structure and language meaning, including lexical, grammatical, and contextual meaning. This study recommends several minor improvements, such as subheading markings, speech element presentation, and the addition of explanatory labels to support readability. Thus, this book is considered suitable for use as a textbook at the elementary school level. The main contribution of this study is to provide an evaluative basis for the development of textbooks that not only comply with the national curriculum but also meet good and correct linguistic standards.